The effects of digitalization to environmental graphic design in the context of urban identity: the example of the led billboard - Akdağ Satır, Dide (Istanbul Kultur Univ, Atakoy Campus, Bakırkoy, Istanbul, 34156, Turkey, 2015)
Cities are the places where changes in all platforms of cultural processes, political life and economical structure in the 21st century are the most intense. With the number of people heading to cities and the corresponding formation of urban space according to the ideological structure of consumer society, the consumption has increased and accordingly changes have begun in advertising and promoting services. In the process of globalization, as a result of digitalisation created by change and formation in technology, it is seen that in the city, which is the base of everything about human, identity, design and visual pollution problems have arisen. One of the elements of this visual pollution during the formation in city is LED boards. In this context, the process and the role of the presence of LED boards is studied argumentatively, with examples in the frame of graphic design, a sensible approach to daily life is aimed to achieve. Having an important place in the life of an urban resident, LED boards with their increasing number is determined to have some problematic figural issues on the colour they include, typography, font characteristics and word space considering their size on the shops and sidings, their positions, and their aggregation, sequence and their evaluation of hierarchal system. Concordantly, some analysis has been performed on pragmatic size of LED boards and some solutions have been intended to put forth. Again, in this part, while different disciplines have been blended, Urban study has been carried out with the graphic design discipline perspective.
Keywords: Environmental Graphic Design; Graphic Design; Visual Identity; LED; Board